Dark fermentation of piggery wastewater and food waste integrated with mixotrophic microalgae cultivation for recyclable and CO2-neutral biohydrogen production - Lapenas, Louie Anciado; De Luna, Mark Daniel G.; Rollon, Analiza P. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Hydrodgen is the fuel of the future mainly due to its high conversion efficiency, recyclability and non-polluting nature. In this study, simultaneous biohydrogen production and biological wastewater treatment was carried out by dark fermentation couplesd with microalgal cultivation. High biohydrogen yields were obtained from the dark fermentative co-digestion of food waste(FW)and piggery wastewater(PW)using a pure culture of Clostridium butyricum Prazamowski (ATTCR 19398TM).The CO2 emissions and high COD soluble metabolities from dark fermentation were converted by Chollera Sorokiniana into valuable biomass.At any VS concentration,hydrogen production was higher with anaerobic co-digestion of feedstocks comapared to anaerobic digestion of individual wasters and the highest hydrogen yield was obtaines at a mixing ration of 80:20 (FW:PW).The cumulative hydrogen production of 12,474.12 ml/L,were obtained for PFW FW and PW,respectively.
Thesis (M.S. in Environmental Engineering)--University of the Philippines Diliman
Keywords: Sewage -- Purification -- Biological treatment -- Philippines; Sewage -- Purification -- Anaerobic treatment -- Philippines; Waste products as fuel -- Philippines; Refuse as fuel -- Philippines